Discrepancy between objective and subjective measures of job stress and sickness absence - David H Rehkopf; Hannah Kuper; Michael G Marmot (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: The aim of this study was to examine the association of the discrepancy between externally and self-assessed measures of work environment with long- and short-term sickness absence. METHODS: The study population included 6997 middle-aged men and women from the Whitehall II cohort, whose work characteristics were examined at baseline (1985-1988) through both an external evaluation and self-report, with a follow-up of up to 13 years of sickness absence reporting from administrative records. The primary exposure of interest was the discrepancy between measures of work stress for fast job pace, conflicting demands, and decision latitude. RESULTS: In mutually adjusted models, external measures of job characteristics were more strongly associated with higher rates of sickness absence compared with self-assessed measures, for both lower frequency of fast work pace and lower conflicting demands (ie "passive" levels). Individuals who self-reported higher frequencies of fast work pace and conflicting demands than were reported through external assessment had higher rates of short-term sickness absence [incident rate ratios (IRR) of 1.13 (95% confidence interval [95% CI] 1.11-1.15) and IRR 1.14 (95% CI 1.11-1.16), respectively]. There was no difference in rates of sickness absence found for decision latitude [IRR 1.02 (95% CI 1.00-1.04)]. CONCLUSIONS: Our findings demonstrate that the discrepancy between externally and self-assessed job demand measures have additional predictive power beyond each individual measure of job structure, which may be related to the extent of cognitive and emotional processing of assessment questions as compared to decision latitude measures.